Bilateral Idiopathic Neuroretinitis - M Hidayat; Rince Liyanti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2019)
Introduction : Neuroretinitis is a clinical entity characterized by acute loss of vision associated with disc edema and a star pattern of exudates in the macula. It can be divided into two, those with a specific infectious agent or idiopathic. Most infectious cases are due to cat-scratch disease, caused by Bartonella species and other infectious agents. Case with a clear infectious are categorized as idiopathic. Most patients with idiopathic neuroretinitis recover excellent visual acuity with or without intervention. Although the presentationis most often unilateral, bilateral cases of neuroretinitis have been reported. Method : A 20 years old woman with a 2-weeks history of sudden progressive visual loss both eyes (visual acuity : RE 3/60; LE 20/200). The optic disc were edema and the hard eksudat on the macular area. Two weeks follow up, funduscopic shows a macular star and the optic disc’s edema were reduced. Perimetric test shows general depressed in both eyes. The blood tests and the brain CT Scan were normal. She received methyl prednisolone 48 mg for 2 weeks. 8 months follow up, VA : RE 20/50, LE 20/40 with the pinhole 20/15 in both eyes. The funduscopic still edema and slightly pale. Results : There was improvement in central visual acuity after steroid treatment, but leave residual abnormal funduscopic. Conclusion: Neuroretinitis is generally self-limited. The visual acuity recover excellent with the steroid, but the abnormal disc in this case related to a vaso-occlusive mechanism of prelamin ararterioles with subsequent disc infraction.